Xanthogranulomatous oophoritis presenting as a pseudotumor of the ovary: a clinical dilemma - Jindal, Dweep; Mankad, Meeta H.; Dave, Pariseema S.; Kamath, Anusha A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Inflammatory Pseudotumor of ovary is a distinct benign entity characterized by the presence of spindle cells mixed with variable amount of lymphocytes and plasma cells. Female genital tract is an unusual location for xanthogranulomatous inflammation and if present usually involves the endometrium. xanthogranulomatous oophoritis is rare and only a handful of cases have been reported. Methods: At The Gujarat Cancer and Research Institute, Ahmedabad; a Regional Cancer Centre we came across two cases of Xanthogranulomatous oophoritis, a rare clinical condition. In view of the rarity of the clinical entity, the cases are summarized and discussed. Results: Xanthogranulomatous oophoritis is a rare clinical entity with very few reported cases. Its pathogenesis involves chronic inflammatory process of unknown origin. Pre-operative diagnosis has been challenging due to non-specific presenting symptoms and radiological imaging. Characteristic microscopic picture includes presence of well-differentiated spindle cells with variable amount of collagenous stroma and presence of inflammatory changes. Immunohistochemistry performed at our institute was found to be positive for CD 68, Vimentin and S-100 for xanthogranulomatous oophoritis. Conclusions: Data from radiological imaging for extra genital xanthogranulomatous inflammation is being extrapolated to determine a pre-operative diagnosis for xanthogranulomatous oophoritis of the genital tract. However, no pathognomic radiological findings are defined at present making histopathological diagnosis the mainstay for diagnosis of this condition. Immunohistochemistry panel markers play a helpful role in the diagnosis when in doubt. Surgery is the definitive mode of treatment providing a good prognosis post operatively.